(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The main objective of the study was to examine the effect of human resource accounting on performance. The effect of HRA learning costs (on the job training, special training and development programmes) on performance was examined. The studied examined the effect of on-the-Job Training costs on performance of Civil servants in Osun State, Nigeria; evaluates the effect of Special Training Costs on performance and examined the impact of Development Program Costs on performance of the respondents. Primary and secondary data were used for the study. Simple random and purposive sampling was used to select three hundred and ten (310) respondents. Ordinary Least Square Regression analysis (OLS) was used to analyze all objectives of the study. The HRA learning cost (on-the-job training cost) have positive and significant effect on employee competence; development program cost have a significant effect on employee competence while special training cost does not have significant effect on the level of competence of the employees. HRA learning cost collectively has positive and significant effect on performance of the respondents. The study concluded that HRA affects organizational performance positively and significantly.